Soil and microbial response to manipulated precipitation and land management - Carter, Tiffany LaRose (Kansas State University, 2019)
Microorganisms play a vital role in maintaining plant and soil health. Within soils, microorganisms are responsible for nutrient cycling and organic matter decomposition. Because soil microbes are sensitive to environmental conditions, they are early indicators of changes in soil health. Soil microbes depend heavily on moisture and substrate availability for growth and survival. Limitation of either factor can alter the survival rates and microbial community function. The objectives of this study were to understand better soil microbial responses to manipulated precipitation and land management by (i) assessing the microbial community composition and soil properties after over 25 years of irrigation in annually burned native prairie; (ii) assessing the effect of long-term irrigation on microbial community respiration response to moisture and substrate addition; and (iii) assessing the soil microbial community and soil structure of degraded agricultural soil under conventional tillage sorghum (CT), no-till sorghum (NT), and replanted big bluestem (RP). The first two objectives were based on a long-term study in a tallgrass prairie where ambient and irrigated transects have been maintained for 25 years. Soil samples were collected four times per year and assessed for soil chemical properties and microbial community structure. The third study used a long-term (17-y) study of ecosystems (replanted big bluestem, and no-till and tilled sorghum). Soil C and N, aggregate structure and microbial community structure were measured. Contrary to previous research, long-term irrigation did not significantly impact the overall microbial community; however, there was a seasonal effect on the microbial community. Fungal PLFA biomarkers increased at the end of each growing season. Because greater soil water content and carbon inputs are known to contribute to fungal dominance, this increase can generally be attributed to seasonal plant growth cycles. Bacterial PLFA biomarkers peaked during the middle of the plant growth cycle indicating the influence of plant inputs on microbial growth. Microbial response to water and glucose addition in the laboratory was significant, indicating a historic effect of irrigation on community composition. For the third objective, soil macroaggregate formation was directly correlated to changes in land management. Macroaggregate fractions were greatest in replanted big bluestem soils, followed by no till and conventional till grain sorghum. No significant differences in soil organic carbon or total nitrogen were observed between ecosystems. Microbial biomass was greatest in RP soils. However, no significant differences were observed between NT and CT soils. This indicates that reduced tillage increased soil aggregation. Because microbial properties are controlled by vegetative growth, as well as soil properties and land management, incorporating known soil health improvement practices may allow nutrient resources and soil structure to improve toward near prairie soil health. Additional research is needed to define further linkages between microbial community composition, microbial function, and overall soil health.
Keywords: Grassland soil; Microbial community; Soil health; Precipitation; Tillage management